HUBUNGAN PREDISPOSING FACTOR DENGAN PERILAKU PENGGUNAAN APD - Muhammad Rizky Andriyanto (Universitas Airlangga, 2017)
The use of Personal Protective Equipment (PPE) is one of the risk control measures that aim to protect workers from safety and health hazards. The purpose of this study was to analyze factors related to the behavior of the use of PPE in Production Unit I PT Petrokimia Gresik. This research was an analytic-observational research with cross sectional design. Sample in this research were 100 workers. The result was presented in the form of frequency distributions and cross-tabulations then analyzed by chi-square statistic. The results showed that the majority of the workers were well behaved in the use of PPE in the workplace. Statistical analysis showed that the knowledge (p = 0.019; r = 0.346) was the significant factors related to the behavior of the use of PPE and have lower relationships. The conclusion was that the higher the level of knowledge, the better behavior in the use of PPE, while suggestions for the company is the need to increase the amount of training related to K3 especially regarding PPE informally, supervisors to be more assertive to punish or sanction against employees who violate the rules, no matter the level of education, age, and length of service, and the need to increase K3-related surveillance and establish good communication with workers. Keywords: behavior, personal protective equipment, policies, Gresik, fertilizers and chemicals